Analisis Hubungan Stres, Aktivitas Fisik, dan Kelelahan Dengan Gangguan Siklus Menstruasi - Priantika, Maulidya Yuni; Syahrul, Fariani (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT UNIVERSITAS NAHDLATUL ULAMA BLITAR, 2023)
The menstrual cycle is the distance between periods. A normal menstrual cycle is 22-35 days. Distances that are more or less are called menstrual cycle disorders. Menstrual cycle disorders are divided into 3 namely polymenorrhea, oligomenorrhea, and amenorrhea. Menstrual cycle disorders often occur in adolescence due to unstable hormonal performance and can be caused by several factors of menstrual cycle disorders including stress activity, physical activity, and fatigue. This study aims to analyze the relationship between physical activity, fatigue, and stress with menstrual cycle disorders in female students of the Faculty of Public Health, Universitas Airlangga. Analytic observational research with the study design used was cross sectional. The sample size was 178 respondents. Data were collected using a questionnaire. The relationship analysis test used chi-square and fisher's exact test. The results of this study obtained the percentage of stress mostly in the moderate category (81.5%), physical activity of female students mostly in the low category (47.2%), and fatigue mostly in the moderate category (76.4%). The prevalence of menstrual cycle disorders was 18.5%. The p-value was 1.0 on the stress variable, 0.869 on the physical activity variable, and 0.354 on the fatigue variable. All variables get a p-value> 0.05. The conclusion of this study is that there is no significant relationship between stress, physical activity, and fatigue with the occurrence of menstrual cycle disorders in female students of the Faculty of Public Health, Universitas Airlangga